Recent Progress in Utilization of Functionalized Organometallic Reagents in Cross Coupling Reactions and Nucleophilic Additions - Chen, Jin-Quan; Dong, Zhi-Bing (Synthesis, 2020)
Organometallic compounds have become increasingly important in organic synthesis because of their high chemoselectivity and excellent reactivity. Recently, a variety of organometallic reagents were found to facilitate transition-metal-catalyzed cross-coupling reactions and nucleophilic addition reactions. Here, we have summarized the latest progress in cross-coupling reactions and in nucleophilic addition reactions with functionalized organometallic reagents present to illustrate their application value. Due to the tremendous contribution made by the Knochel group towards the development of novel organometallic reagents, this review draws extensively from their work in this area in recent years.Introduction1 Transition-Metal-Catalyzed Cross Couplings Involving Organozinc Reagents2 Transition-Metal-Catalyzed Cross Couplings Involving Organomagnesium Reagents3 Transition-Metal-Free Cross Couplings Involving Zn and Mg Organometallic Reagents4 Nucleophilic Additions Involving Zn and Mg Organometallic Reagents5 Cross-Coupling Reactions or Nucleophilic Additions Involving Mn, Al-, La-, Li-, Sm- and In-Organometallics6 Conclusion
Keywords: organometallic reagent; cross coupling; nucleophilic addition; transition-metal catalyst; synthesis